FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PENCEGAHAN COVID-19 DI KABUPATEN SUKOHARJO, JAWA TENGAH - Azmiardi, Akhmad; Sari, Dewi Puspito (MEDIA ILMU KESEHATAN, 2020)
Background: Covid-19 is an emerging infectious disease that poses a significant threat to public health. Preventive measures play an important role in reducing infection rates and controlling the spread of disease Objective: This study aimed to determine factors influence Covid-19 prevention behavior in Sukoharjo. Methods: This was a cross-sectional study conducted in Sukoharjo, Central Java in April 2020. A total of 246 research subjects were obtained using simple random sampling. The dependent variable in this study was the prevention behavior. The independent variables in this study were age, education, occupation, income, knowledge, and attitudes. The data was obtained using online questionnaire and analyzed using multiple logistic regression Results: The were 226 people (91.87%) using face mask, 199 people (80.89%) regularly washing their hands and 130 people (52.85%) practice social distancing. Education >high school (OR= 3.69; 95%CI= 1.42-9.56; p= 0.007), Income >1.8 million/month (OR= 2.90; 95%CI= 1.29-6.52; p= 0.010). High knowledge (OR= 2.25; 95%CI= 1.04-4.83; p= 0.037) and a positive attitude (OR= 5.18; 95%CI= 2.36-11.37; p <0.001) were increased preventive behavior.. Conclusion: higher education, income level, knowledge, and positive attitude are increase Covid-19 prevention behavior.